2017
DOI: 10.1007/jhep09(2017)052
|View full text |Cite
|
Sign up to set email alerts
|

Displaced lepton flavour violating signatures of right-handed sneutrinos in U(1)′ supersymmetric models

Abstract: We consider a U(1) extended supersymmetric model with a right-handed neutrino superfield which can generate light neutrino mass by Type I seesaw mechanism. The lighter superpartner of the right-handed neutrino could be the scalar dark matter. These right-handed sneutrinos can come from the decay ofZ , superpartner of the extra gauge boson Z . Left-right handed sneutrino mixings affect their decays further, giving rise to displaced "lepton flavour violating" signatures. A wino-like chargino NLSP (next to lighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A very small decay width of 7.58 × 10 −17 GeV easily gives rise to O(2) meter displaced charged Higgs boson decay. [15,[91][92][93][94][95][96] Next we focus on the production cross-sections of the chosen benchmark points at the LHC with centre of mass energy of 14, 100 TeV [97]. In Table 3 present the cross-sections of various associated Higgs production modes at the LHC with centre of mass energy of 14 and 100 TeV.…”
Section: Lhc Phenomenologymentioning
confidence: 99%
“…A very small decay width of 7.58 × 10 −17 GeV easily gives rise to O(2) meter displaced charged Higgs boson decay. [15,[91][92][93][94][95][96] Next we focus on the production cross-sections of the chosen benchmark points at the LHC with centre of mass energy of 14, 100 TeV [97]. In Table 3 present the cross-sections of various associated Higgs production modes at the LHC with centre of mass energy of 14 and 100 TeV.…”
Section: Lhc Phenomenologymentioning
confidence: 99%
“…Displaced Higgs production in a supersymmetric Type-III seesaw mechanism is already looked into [28]. In general, the seesaw models with lower couplings predict displaced decays of right-handed neutrinos in case of Type-I seesaw [67,68] but we do not expect any flying charged track in those scenarios. In case of Type-III seesaw at the LHC, N ± gives charged track before it decays, whereas N 0 has invisible track before the decay.…”
Section: Discussionmentioning
confidence: 83%
“…Finalstates of 4 , 3 + ≥ 1j, 2 + ≥ 2j are also studied as we found that MATHUSLA regions are preferred by BP2, BP3 for Y N = 5 × 10 −8 , 5 × 10 −9 , respectively. To complete the study we drew the regions plots in M N − M Z B−L (in Figure 12), M Z B−L − Y N (in Figure 13) and M N − Y N (in Figure 14) planes, where in Figure 13 The study performed in this article can be easily attributed to other U (1) models with righthanded neutrino [67][68][69][70] and other displaced neutral decays [71,72]. The segregation of transverse and longitudinal displaced decays manifests the longitudinal boost effect at higher centre of mass energies.…”
Section: Discussionmentioning
confidence: 99%